FOLFOXIRI plus cetuximab as conversion therapy for unresectable RAS/BRAF wild-type left-sided colorectal cancer with liver-limited metastases: a prospective dual-center pilot study - Yang, Wenwei; Chen, Dong; Niu, Yaru; Wu, Guifu; Huang, Zhangkan; Bi, Xinyu; Zhao, Hong; Che, Xu; Sun, Yongkun (Frontiers in Oncology, 2024)
To explore the efficacy and safety of FOLFOXIRI plus cetuximab regimen as conversion therapy for patients with unresectable RAS/BRAF wild-type colorectal liver-limited metastases (CLM).This was a dual-center, phase II trial with the rate of no evidence of disease (NED) achieved as the primary endpoint. All enrolled patients with initially unresectable left-sided RAS/BRAF wild-type colorectal liver-limited metastases received a modified FOLFOXIRI plus cetuximab regimen as conversion therapy.Results: Between October 2019 and October 2021, fifteen patients were enrolled. Nine patients (60%) achieved NED. The overall response rate (ORR) was 92.9%, and the disease control rate (DCR) was 100%. The median relapse-free survival (RFS) was 9 (95% CI: 0-20.7) months. The median progression-free survival (PFS) was 13.0 months (95% CI: 5.7-20.5), and the median overall survival (OS) was not reached. The most frequently occurring grade 3-4 adverse events were neutropenia (20%), peripheral neurotoxicity (13.3%), diarrhea (6.7%), and rash acneiform (6.7%).The FOLFOXIRI plus cetuximab regimen displayed tolerable toxicity and promising anti-tumor activity in terms of the rate of NED achieved and response rate in patients with initially unresectable left-sided RAS/BRAF wild-type CLM. This regimen merits further investigation.